MATHEMATICAL FRACTIONAL MODELING OF TRANSPOT PHENOMENA OF VISCOUS FLUID-FLOW BETWEEN TWO PLATES - Asadullah, Muhammad; Raza, Ali; Ikram, Muhammad Danish; Asjad, Muhammad Imran; Naz, Rabia; İnç, Mustafa (Vinca Inst Nuclear Sci, 2021)
This work is about the mass and heat transfer flow for adhesive fluid between two upright plates pulled apart by a distance, d. Fractional model of the considered problem is developed after making governing equations dimensionless. Laplace transform technique is utilized to acquire analytical solutions and some graphics are presented to see the physical behavior of embedded parameters.
Keywords: MHD; viscous fluid; fractional modeling; heat and mass transfer